Giải các phuơng trình sau: 7. (3x+2) (x-5) = (2x-5) (2+3x) 8. (2x-1) ²+(2-x) (2x-1) =0 9. (2-3x) ²=(2-3

Giải các phuơng trình sau:

7. (3x+2) (x-5) = (2x-5) (2+3x)

8. (2x-1) ²+(2-x) (2x-1) =0

9. (2-3x) ²=(2-3x) (2-5x)

10.(x-3) ²=(3-x) (2-5x)

2 bình luận về “Giải các phuơng trình sau: 7. (3x+2) (x-5) = (2x-5) (2+3x) 8. (2x-1) ²+(2-x) (2x-1) =0 9. (2-3x) ²=(2-3”

  1. 7. (3x + 2)(x – 5) = (2x – 5)(2 + 3x)
    ⇔ 3x² – 15x + 2x – 10 = 4x + 6x² – 10 – 15x
    ⇔ 3x² – 15x + 2x – 4x – 6x² + 15x = -10 + 10
    ⇔ -3x² – 2x = 0
    ⇔ -x(3x + 2) = 0
    ⇔ [(-x=0),(3x+2=0):} ⇔ [(x=0),(x=-2/3):}
    Vậy …………
    8. (2x – 1)² + (2 – x)(2x – 1) = 0
    ⇔ 4x² – 4x + 1 + 4x – 2 – 2x² + x = 0
    ⇔ 2x² + x – 1 = 0
    ⇔ 2x² + 2x – x – 1 = 0
    ⇔ 2x(x + 1) – (x + 1) = 0
    ⇔ (x + 1)(2x – 1) = 0
    ⇔ [(x+1=0),(2x-1=0):} ⇔ [(x=-1),(x=1/2):}
    Vậy ………….
    9. (2 – 3x)² = (2 – 3x)(2 – 5x)
    ⇔ 4 – 12x + 9x² = 4 – 10x – 6x + 15x²
    ⇔ -12x + 9x² + 10x + 6x – 15x² = 4 – 4
    ⇔ 4x – 6x² = 0
    ⇔ 2x(2 – 3x) = 0
    ⇔ [(2x=0),(2-3x=0):} ⇔ [(x=0),(x=2/3):}
    Vậy ………….
    10. (x – 3)² = (3 – x)(2 – 5x)
    ⇔ x² – 6x + 9 = 6 – 15x – 2x + 5x²
    ⇔ x² – 6x + 15x + 2x – 5x² = 6 – 9
    ⇔ -4x² + 11x = -3
    ⇔ -x(4x – 11) = -3
    ⇔ x(4x – 11) = 3
    ⇔ [(x=3),(4x-11=3):} ⇔ [(x=3),(x=7/2):}
    Vậy ……….
    Xin 5s và ctlhn nha!

    Trả lời

Viết một bình luận

Câu hỏi mới